Intervalo entre partos en ganado criollo Chino Santandereano (1989)
Every project of criollo breeds recovery must include productive traits studies. Fertility is the most important economic trait in beef cattle. Calving interval is one of the measurements of fertility and it is influenced by enviromental factors. So, it is very important to study the effect of such factors in order to make an appropriate reproductive herd management. The main objective of the present work was to study the influence of year of calving, season of calving, age of dame, sex of calf, breed of sire and type of insemination (natural or artificial) on the calving interval of a Chino Santandereano herd. The data were analysed by last squares methods (G.L.M. of S.A.S. with sum of squares type Ill), the effects of year of calving, age of cow and type of insemination were significant (P < 001). The overall mean for natural insemination was 435.4 days, whereas for artificial insemination was 534.1 days. With only one exception, calving intervals showed a Continuous decrease of lenght starting with cows less than 3 years of age (525.4. days) to cows 10 years of age (432.8 days). The exception, cows 3 to 4 years old, had a mean of 530.4 days.